2003
DOI: 10.1104/pp.102.018572
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Ester Formation in Roses. Identification of an Acetyl-Coenzyme A. Geraniol/Citronellol Acetyltransferase in Developing Rose Petals

Abstract: The aroma of roses (Rosa hybrida) is due to more than 400 volatile compounds including terpenes, esters, and phenolic derivatives. 2-Phenylethyl acetate, cis-3-hexenyl acetate, geranyl acetate, and citronellyl acetate were identified as the main volatile esters emitted by the flowers of the scented rose var. "Fragrant Cloud." Cell-free extracts of petals acetylated several alcohols, utilizing acetyl-coenzyme A, to produce the corresponding acetate esters. Screening for genes similar to known plant alcohol acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
150
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(166 citation statements)
references
References 33 publications
3
150
1
5
Order By: Relevance
“…This showed that the individual reaction of a fragrance ingredient has a specific varietal activity. Shalit et al (2003) reported that acetate esters are produced from alcohol-based compounds by acylation reactions catalyzed by alcohol acetyltransferase (AAT). When AAT obtained from rose petals was added to various types of alcohol-based compounds, all of the compounds showed acylation activity, although the activities differed with the various compounds used.…”
Section: Discussionmentioning
confidence: 99%
“…This showed that the individual reaction of a fragrance ingredient has a specific varietal activity. Shalit et al (2003) reported that acetate esters are produced from alcohol-based compounds by acylation reactions catalyzed by alcohol acetyltransferase (AAT). When AAT obtained from rose petals was added to various types of alcohol-based compounds, all of the compounds showed acylation activity, although the activities differed with the various compounds used.…”
Section: Discussionmentioning
confidence: 99%
“…In addition a large number of petal expressed cDNAs have been identified and stored in databases (14,23,27,28). Genes involved in scent production were identified: sesquiterpene synthase (23), alcohol acetyl transferase (50), O-methyltransferases (32,48,49). Transciption factors controlling the rose floral development have also been identified and cloned (36).…”
Section: Perspectives For Marker Assisted Breedingmentioning
confidence: 99%
“…The volatile component compositions were different between fresh rose flowers and hydrosols (Table 1). Fresh flowers contained 3,5-dimethoxy toluene (13.0%, reported as a tea-like odor) (Cherri-Martin et al, 2007) and cis-3-hexenyl acetate (12.5%, reported as a fruity and green-leaves like odor) (Morales and Aparicio, 1999;Shalit et al, 2003) as major components. A high amount of 3,5-dimethoxy toluene has been confirmed in hybrid tea roses (Joichi et al, 2005).…”
Section: Volatile Component Compositions Of Fresh Rose Flowers and Hymentioning
confidence: 99%